Preparation of Chitosan-Fe3O4 Nanoparticles by In-situ Co-Precipitation Using Tripolyphosphate / Citrate as Crosslinker and Characterization Using XRD - Vita Tria Mardila; Akhmad Sabarudin; Djoko Herry Santjojo (Natural B, Journal of Health and Environmental Sciences, 2016)
Chitosan-Fe3O4 nanoparticles have been synthesized in a one pot reaction by combine TPP: citrate as crosslinker. The method was in-situ co-precipitation of iron salts in the presence of chitosan and crosslinker. The aim of this study was to determine the effect of preparation process towards chitosan-Fe3O4 nanoparticles characteristics which was prepared on several preparation condition: chitosan:Fe(II):Fe(III) ratio, TPP:citrate ratio, and crosslinking time. The crystallite sizes of the Fe3O4 and chitosan- Fe3O4 nanoparticles was obtained from modified Debye Scherrer equation using data from XRD analysis. The crystallite size of the bare-Fe3O4 and chitosan-Fe3O4 nanoparticles were found to be about 6.22 and 9.49 nm, respectively. XRD analysis results shown that beside Fe3O4 phases there was γ-Fe2O3 phase due to the oxidation of Fe3O4.The crystallite sizes and the percentage of Fe3O4 decreases with increasing number of chitosan coating the Fe3O4 and the length of crosslinking time